2010
DOI: 10.1089/cbr.2009.0740
|View full text |Cite
|
Sign up to set email alerts
|

Review of Positron Emission Tomography Tracers for Imaging of Tumor Hypoxia

Abstract: Hypoxia plays a critical role in tumor development and aggressiveness and is an important prognostic factor for resistance to antineoplastic treatments; therefore, it is required to measure the hypoxic level of tumor for a favorable outcome. The pretherapy information on the oxygenation status of a tumor microenvironment should also have implications for treatment selection. A diffuse distribution of hypoxia in a tumor might suggest a benefit from a systemic approach, such as a hypoxic cell cytotoxin, tirapaza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 45 publications
2
20
0
Order By: Relevance
“…Hence, the alternative hypothesis of indirect CD137 enhancing effects mediated by genes upregulated by the transcriptional activity of HIF-1α is under investigation. In fact, previous reports have revealed a functional interplay of HIF-1α and NF-κB members (44), whereas canonical NF-κB sites are leading inducers of the CD137 promoter (10). In fact, CD137 upregulation in our experiments seems to take place mainly at the transcriptional level.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Hence, the alternative hypothesis of indirect CD137 enhancing effects mediated by genes upregulated by the transcriptional activity of HIF-1α is under investigation. In fact, previous reports have revealed a functional interplay of HIF-1α and NF-κB members (44), whereas canonical NF-κB sites are leading inducers of the CD137 promoter (10). In fact, CD137 upregulation in our experiments seems to take place mainly at the transcriptional level.…”
Section: Discussionsupporting
confidence: 56%
“…First, we found that in tumors in which we detect CD137 + , TILs are indeed undergoing hypoxia as documented on living mice by sensitive 18 F-MISO positron emission tomographic (PET) imaging based on imidazole chemistry (10). This property applies both to transplanted (CT26, MC38, B16-OVA) and spontaneous tumors ( Supplementary Fig.…”
Section: Hypoxia Upregulates Cd137 Expression On T Cellssupporting
confidence: 61%
“…Franzius et al reported no differences in tumor uptake among the subtypes of the conventional-type osteosarcoma-that is, osteoblastic, fibroblastic, and chondroblastichowever, no reports are found evaluating possible differences in 18 F-FDG uptake among the different types of osteosarcoma (12). 18 F-FMISO is an indicator of hypoxia that diffuses passively into cells and is retained only in hypoxic areas after a 2-electron reduction reaction (13). It is well established that hypoxia is associated with aggressive tumor phenotype and with pronounced chemoresistance dependent on the higher expression and stabilization of the heterodimeric hypoxia-inducible factor complex and on the overexpression of direct targets such as carbonic anhydrase IX (CaIX), which is associated with worse prognosis and lower survival in several tumors (13,14).…”
mentioning
confidence: 99%
“…18 F-FMISO is an indicator of hypoxia that diffuses passively into cells and is retained only in hypoxic areas after a 2-electron reduction reaction (13). It is well established that hypoxia is associated with aggressive tumor phenotype and with pronounced chemoresistance dependent on the higher expression and stabilization of the heterodimeric hypoxia-inducible factor complex and on the overexpression of direct targets such as carbonic anhydrase IX (CaIX), which is associated with worse prognosis and lower survival in several tumors (13,14). In osteosarcoma, high levels of hypoxiainducible factor 1a in tumor tissue and a high serum level of the transcription product of its target gene, vascular endothelial growth factor, are associated with a poor prognosis (15,16).…”
mentioning
confidence: 99%
“…Left intensity-modulated radiation therapy to the hypoxic tumour subregion, may be helpful in situations of focal as opposed to diffuse tumour hypoxia (Imam, 2010 ). Nitroimidazoles, of which the most important is 18F-fl uoromisonidazole (FMISO) (see Plate VI in the colour section between pages 182 and 183), are organic compounds that also include the antibiotic metronidazole.…”
Section: Hypoxia-specifi C Tracersmentioning
confidence: 99%